Exergy-economic analysis and evaluation method of park-level integrated energy system - Mo, Lili; Liu, Xin; Chen, Haoyong; Zhao, Zhendong; Chen, Jinbin; Deng, Zeyu (Frontiers in Energy Research, 2022)
The park-level integrated energy system (PIES) has been developing rapidly in recent years due to its economic and environmental advantages. PIES is a typical user-side energy supply system with multiple energy forms such as solar energy, electrical energy, cool energy, and heat energy inside the system. The coupling between these energy sources and the differences in the quality of these energy sources make its analysis and evaluation a difficult task for PIES research. In order to solve the problems, an analysis and evaluation method of PIES based on exergy economics is proposed, which lays the foundation for the subsequent optimization of system operation. First, a unified analysis model of PIES is developed based on exergy economics theory. Second, the corresponding analysis and evaluation method for this model is proposed. In this method, the exergy efficiency and exergy loss are used as the evaluation index of system energy consumption characteristics, while the exergy loss cost and exergy economic coefficient are used as the evaluation index of system economic characteristics. Meanwhile, an evaluation procedure for using this method is also designed. Lastly, the effectiveness of the given approach is validated in a PIES case in Guangzhou. The results show that the proposed model can accurately calculate the exergy cost of each energy link. The proposed evaluation method can not only analyze the performance of subsystems within a single system but also compare the advantages and disadvantages between different systems.